IMPLEMENTASI ASUHAN KEBIDANAN BERKELANJUTAN (CONTINUITY OF CARE) DI PUSKESMAS MOJOTENGAH WONOSOBO - Dewi Candra Resmi; Indrawati Aris Tyarini; Farihah Indriani; Sawitri Sawitri (Fakultas Ilmu Kesehatan (FIKES) Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2022)
Purpose: Maternal Mortality Rate (MMR) is an indicator used to determine the health status of pregnant, maternity and postpartum women; Chronic Energy Deficiency (KEK) is a condition where mothers suffer from chronic food shortages. Seeing the large Maternal Mortality Rate (MMR) in Wonosobo, one of which in 2021 is caused by KEK/malnutrition, the author is interested in studying and providing comprehensive midwifery care Methods: This type of research uses descriptive methods with a continuity of care approach. The research subject in this case is Mrs. T aged 29 years G2P1A0 with KEK at the Mojotengah Community Health Center, from 6 June 2021 to 17 July 2021. Results: In pregnancy there were CED complications, during delivery there were CED complications, the baby was born spontaneously, there were no BBL abnormalities until the neonate, the postpartum period was normal, the mother temporarily used MAL contraception. Conclusion: Comprehensive midwifery care found complications, namely CED, but there were no complications in the baby.